Internet and social media use for antibiotic-related information seeking: Findings from a survey among adult population in Italy - Zucco, Rossella; Lavano, Francesco; Anfosso, Rosa; Bianco, Aida; Pileggi, Claudia; Pavia, Maria (International journal of medical informatics (Shannon, Ireland), 2018)
•The study establish the extent of Web use to gather information about antibiotics.•A cross-sectional study was conducted among parents of public school students.•Parents have high Internet use and a desire to learn about antibiotic use via web.•Internet and social media can be useful for the dissemination of valid information. The Internet represents an increasingly common source of health-related information. Internet and Social Media can be used to promote a prudent use of antibiotics. To establish the extent of Internet and Social Media use to search for antibiotic related information and the potential implications in health care among adult population in Italy. This cross-sectional study was conducted from March to May 2017, among a sample of parents of public school students. A 2-stage cluster sample design was planned. An informed consent form and a questionnaire were given to selected students to deliver to their parents. The questionnaire included questions on knowledge, attitudes, and behavior toward antibiotic use, and questions about Internet use to gather information about antibiotics. A total of 913 parents completed the questionnaire, with a 67.4% response rate; 22.1% did not know when it was appropriate to use antibiotics. 32.3% of parents reported self-medication with antibiotics. 73.4% of respondents used the Internet to search for information about antibiotic use. Among social networks users, 46.5% reported the use of these media to get information about antibiotics and 45% of instant messaging app users share information about antibiotics. The results of the multiple logistic regression analysis showed that Internet use to search for antibiotic-related information was higher among females, younger subjects, with a higher level of education, in those who reported self-medication with antibiotics and in those who needed additional information on side effects of antibiotics from the GP compared with those who did not need any additional information. Internet use was significantly less likely in participants with cardiovascular diseases and cancer compared with those without chronic conditions, and in those who reported to strongly agree/agree, or were uncertain about antibiotic use without a GP prescription, compared with those who reported to be disagree/strongly disagree. Internet and social media are widely used for antibiotic-related information seeking in the Italian population. Health organizations must consider social media within their communication strategy to promote the appropriate Web use for antibiotic-related information seeking in the general population, although more evidence is needed regarding the optimal mix of communication interventions.